2001
DOI: 10.1007/bf02913527
|View full text |Cite
|
Sign up to set email alerts
|

Coexistence of lung cancer and hamartoma

Abstract: We present a rare case of a synchronous primary lung cancer adjacent to a hamartoma. A 71-year-old woman was admitted with congestive heart failure due to acute myocardial infarction. A chest radiogram on admission showed pulmonary edema with a tumor shadow in the right upper lung field. Because histological diagnosis was not obtained preoperatively, a wedge resection of the lung was conducted using video-assisted thoracoscopic surgery. The histopathological examination confirmed the coexistence of an adenocar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
10
0
3

Year Published

2003
2003
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 7 publications
0
10
0
3
Order By: Relevance
“…The typical pulmonary hamartoma is made up of benign-appearing mesenchymal fibromyxoid tissue with a variable extent of chondroid differentiation, fat, fibrous tissue, and smooth muscle, 6,30,39,73 associated with long-branching clefts of presumably non-neoplastic ciliated and nonciliated bronchial epithelium. 15,69 Though pulmonary hamartomas are benign neoplasms, an increased risk for the concurrent development of lung cancers, (especially adenocarcinoma of the same pulmonary lobe 1,8,22,29,33,60,71,75,79 ) has been reported. Exceedingly rare is the development of tumors within the hamartoma, such as carcinomas, 21,32,58,62,66,72,77,84 sarcomas, 2,3,50 or salivary gland-type tumors.…”
mentioning
confidence: 98%
“…The typical pulmonary hamartoma is made up of benign-appearing mesenchymal fibromyxoid tissue with a variable extent of chondroid differentiation, fat, fibrous tissue, and smooth muscle, 6,30,39,73 associated with long-branching clefts of presumably non-neoplastic ciliated and nonciliated bronchial epithelium. 15,69 Though pulmonary hamartomas are benign neoplasms, an increased risk for the concurrent development of lung cancers, (especially adenocarcinoma of the same pulmonary lobe 1,8,22,29,33,60,71,75,79 ) has been reported. Exceedingly rare is the development of tumors within the hamartoma, such as carcinomas, 21,32,58,62,66,72,77,84 sarcomas, 2,3,50 or salivary gland-type tumors.…”
mentioning
confidence: 98%
“…19 Subsequent studies also concluded that there was a small but significantly increased risk. 18,20 These authors were, however, not able to define a pathophysiologic link between hamartomas and associated lung cancer. Conversely, the search leading to a diagnosis of malignant lung cancer could incidentally lead to the discovery of an asymptomatic hamartoma.…”
Section: Discussionmentioning
confidence: 97%
“…21 Given the uncertainty, however, it is currently suggested that patients diagnosed with a hamartoma have a complete evaluation to rule out lung cancer. 18,20 The components of this complete evaluation are not defined but should probably include a CT of the chest. None of our 3 patients have radiographic or endoscopic evidence for lung cancer.…”
Section: Discussionmentioning
confidence: 99%
“…[8][9][10] Yayınlarda hamartom ile karsinomun genellikle aynı lobda olduğu, [9,10] hamartomun kanser gelişim sürecine zemin hazırlayabileceği, bu olguların çoğunlukla geç-orta yaşlı erkekler olduğu ve adenokarsinomun daha sık görüldüğü belirtilmiştir. [10] Olgumuzda cinsiyet ve karsinom türü bu bulgulara benzer olmakla birlikte, hamartom ve kanserin ayrı loblarda olması farklılık göster-mektedir.…”
Section: Discussionunclassified